PENGENALAN PERANGKAT KOMPUTER DASAR PADA SDI WAIOTI MAUMERE - Yosafat Pati Koten; Agustinus Lambertus Suban; Nur Hadi; Margaretha Paulina Novianty Rozady; Conshita Junita Chandra; Theresia Wihelmina Mado; Claudia Betruchy Bada; Yohanes Brekmans M Darkel; Maria Wilhelmina Lodan; Lindiana Ermilinda; Henderikus Basilius Nong Muda (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2023)
Introduction to Computer Hardware and Microsoft Basic Training is extremely important for elementary school students, college students, and even working professionals in today's digital age. There is an increasing demand for its use from various groups, both in the office sector and in the educational world. Therefore, as part of our community service, we aim to improve the knowledge and understanding of SDI Waioti Maumere primary school students, familiarize them with computers, fill and understand basic Microsoft forms in Word, and support their skills. Training activities have begun. SDI Waioti Maumere students adapt to life. In this era of advancing globalization. The implementation phases of this service are preparation, implementation, and evaluation. In this activity the service team succeeded in carrying out basic computer and Microsoft Word training for 36 female students and were divided into two classes, namely class A and class B, each with 18 students per class. This can be seen in the enthusiasm of the children who participated in the activities. As a result of this activity, SDI Waioti Maumere students will be able to understand and use the technology gained through their training